Deep Learning Advancements in Breast Cancer Lesion Detection Using U-Net Methodologies (International Journal of Food and Nutritional Sciences, 2019)
The Breast cancer remains a critical global health concern, involves advanced diagnostictools for early detection of breast cancer and advanced scanning methodologies helps doctors,medical practioners for easy diagnotistics and to improve patient health. This researchexplores the application of deep learning methodologies, specifically focusing on the U-Netarchitecture, to enhance the accuracy and efficiency of breast cancer lesion detection